Mop top story and pictures - Freeman, Don 1908-1978. ([New York] Puffin Books, 1978)
An almost-six-year-old with a mass of floppy red hair tries to postpone the inevitable trip to Mr. Barberoli's barber shop.
Reprint of the ed. published by Viking Press, New York.
Keywords: Hair -- Care and hygiene -- Fiction